Utilization Different Macroalgae to Enhance Growth and Survival Rate of Juvenile Abalone, Haliotis squamata: - Chrisoetanto P Pattirane; Aripudin; Asep Suryana; Herlin Kawati (Jurnal Moluska Indonesia, 2023)
As a herbivorous organism, abalone is highly dependent on the availability of macroalgae as its main feed. The types of macroalgae commonly used as abalone feed are Ulva sp (green algae) and Gracilaria sp (red algae). The use of brown algae is still very rare so further research needs to be done. This research was conducted at the Superior Shrimp and fishery production center (BPIU2K) in Bali. The rearing tank used is a fiber tub measuring 200x100x60 cm3. The rearing container used is a plastic basket measuring 40x30x10 cm3. The baskets used were nine pieces, including three baskets each for Gracilaria sp. (pink color), Ulva sp. (blue color), and Padina sp. (green color). The stocking was carried out in the morning by as many as 216 individuals with a stocking density of 2 ind/L/basket. The average size of the shell length is 3.1 cm and the average weight is 6.04 g. Feeding is done once every two days ad-libitum, among other types of Gracilaria sp., Ulva sp., and Padina sp. Observation of water quality is carried out every day including temperature, DO, salinity, and pH. The siphoning of the bottom of the container is carried out every two days. Juvenile abalone maintenance is done by using a completely randomized design (RAL) consisting of three feed treatments namely Gracilaria sp. (A1), Ulva sp. (A2), and Padina sp. (A3), and repeated three times. The ANOVA results of abalone juvenile growth showed no statistically different values (P>0.05) but visually visible differences. The length and width of the shell of juvenile abalone fed Gracillaria sp., Ulva sp., and Padina sp. respectively, 4.1 cm and 2.6 cm; 4.0 cm and 2.4 cm; 3.8 cm and 2.3 cm. Weight of abalone juveniles respectively 12.50 g (Gracillaria sp.), 10.83 g (Ulva sp.), and 9.20 g (Padina sp.). Juveniles fed Gracilaria sp. and Ulva sp. showed 100% survival while juveniles fed Padina sp., it has a survival rate of 98.61%.